Dampak collectivism pada hubungan antara moral reasoning dan whistleblowing - Arya Samudra Mahardhika; Anton Prasetyo (Faculty of Economics and Business, Jenderal Soedirman University, 2019)
The purpose of this study was to analyze the impact of collectivism culture on the relationship between moral reasoning and whistleblowing in government organizations in Kebumen District. The sample in this study were 80 treasurers and village financial staff in Kebumen Regency who met the established criteria. This study uses structural equation modeling (SEM) with WarpPls software version 6. The results of hypothesis testing in this study indicate that a high level of moral reasoning has been proven empirically to increase one's tendency to do whistleblowing, however, collectivism has been proven to empirically reduce whistleblowing tendencies; the latest finding is that collectivism has proven to weaken the relations of moral reasoning and whistleblowing.